Impact of Implementation Merdeka Curriculum on Improving Competence and Performance Christian Religious Teachers Based on Mark 1:21-28 in City of South Tangerang - Sri Seven Yarnitien Zalukhu; Maria Titik Windarti (International Perspectives in Christian Education and Philosophy, 2025)
This study aims to examine the impact of the implementation of the Merdeka Curriculum on improving the competence and performance of Christian Religious Education teachers based on Mark 1:21–28 in South Tangerang City. The Merdeka Curriculum, launched in 2022, was designed as a solution for student-centered and differentiated learning. The research focuses on analyzing teachers’ lack of understanding in preparing differentiated learning, the suboptimal imple-mentation of project-based learning, and the relationship between the implementation of the Merdeka Curriculum and the improvement of teachers’ competence and performance. The study was conducted within the Ministry of Religious Affairs, South Tangerang City, Banten Province, with a population of 61 Christian Religious Education teachers. Data were collected through questionnaires and analyzed using Microsoft Excel 2010 and SPSS 25 for Windows with a quantita-tive approach, regression analysis, and linearity testing. The results show that the implementation of the Merdeka Curric-ulum has a positive impact on teacher competence (87.2%) and performance (86.3%). These findings align with Jesus’ teaching principles in Mark 1:21–28, namely authoritative teaching that produces tangible impact, serving as a theological foundation for improving teaching quality. In conclusion, the better the implementation of the Merdeka Curriculum, the higher the competence and performance of Christian Religious Education teachers in South Tangerang City.